Post-evaluation of the strategic projects of the Directorate of Public Municipalities - Case study for the period (2004-2015 - سعيد, سناء عبد الرحيم; مسلم, حاتم عطا (Journal of Economics and Administrative Sciences, 2018)
The research aims at conducting a follow-up evaluation of a number of strategic projects implemented by the Directorate of Public Municipalities, one of the Ministry of Construction, Housing and Municipalities and Public Works. The sample included (35) varied strategic projects implemented in most Iraqi governorates. Buildings, municipal buildings, minarets, massacres, multi-story parking, paving and rehabilitation of streets and residential neighborhoods. The difference between the actual and planned times and costs of these projects was then measured and analyzed. These projects were used as a tool for collecting data and information. The questionnaire included four axes, each representing one of the parties to the project, which may be a cause of delay (employer, contractor, consultant, etc.) in an attempt to explore as many views as possible. And the results of the research were obtained through the use of the statistical program (SPSS). The most important recommendations of the research were the need to develop appropriate policies and controls for decision-making and development of these policies in accordance with the interest of the work, in order to save the decision maker time to make the right decisions, and the need to study the project documents in depth in order to avoid errors during implementation, And to minimize the additional work as much as possible because of the negative impact on the time and cost of the project, and the need to work on the implementation of the prequalification program for contractors and companies, and attention to the continuation of the process of training and development (Project management fundamentals, planning, organization, risk management, feasibility study, quality management, time management), project management and project management. , As well as attention to the information provided by feedback on the employees and give importance to the administrative organization and performance reports related to the development of workers.